L’hallucination de la connaissance : La Tentation de saint Antoine de Flaubert - Dagmar Stöferle (Flaubert: Revue Critique et Génétique)
Representing the demons in La Tentation de saint Antoine, Flaubert transforms a Christian conception into a psychological one.  More precisely, he uses the concept of “hypnagogic hallucination” of Alfred Maury. But it is only when comparing the different versions of the text that one can observe this process of substitution.  In the 1849 version, the apparitions are always called “demons”.  This earlier, Christian concept seems to have its provenance in the Christliche Mystik by Joseph von Görres which Flaubert read in the French translation of Charles Sainte-Foi (La mystique divine, naturelle et diabolique, Paris, 1862). Görres makes the difference between a “true” Christian mysticism and a “false” demonical mysticism. What is called ecstasy on the one hand, is demonic possession on the other.  Demonology is explained by a heretic conception of evil which is based on a false substantialisation and illustrated most prominently by Manicheism.  As is well-known, Antoine is very attracted by the Gnosis, this – literally translated – religion of cognition.  With the adherers of Gnosis he shares the dualism of a material, terrestrial world and a divine, otherworldly prime principle.  Hence, the basic question is whether he finally overcomes this dualism by acquiring “gnosis” or whether the dualisms persist in the text.  The reading of the Tentation leads to a double result : From a macrostructural point of view, the allegoric resistance of the text indicates a non-overcoming of the dualism.  However, there is one moment of overcoming at the end of the text, a single moment of inversion of monism (être-dans-le-monde) and dualism (acosmisme).